2023
DOI: 10.3390/ijms24076168
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA Adenine Methylation in Caenorhabditis elegans after Multigenerational Exposure to Silver Nanoparticles and Silver Nitrate

Abstract: Multigenerational and transgenerational reproductive toxicity in a model nematode Caenorhabditis elegans has been shown previously after exposure to silver nanoparticles (Ag-NPs) and silver ions (AgNO3). However, there is a limited understanding on the transfer mechanism of the increased reproductive sensitivity to subsequent generations. This study examines changes in DNA methylation at epigenetic mark N6-methyl-2′-deoxyadenosine (6mdA) after multigenerational exposure of C. elegans to pristine and transforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, when the nematodes were intoxicated with AgNO 3 , an increase in global DNA methylation was detected. This led the authors to hypothesize the existence of different epigenetic marks for AgNPs and AgNO 3 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the nematodes were intoxicated with AgNO 3 , an increase in global DNA methylation was detected. This led the authors to hypothesize the existence of different epigenetic marks for AgNPs and AgNO 3 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the vast majority of published findings have focused on the multigenerational imprint of NPs on developmental and reproductive parameters [ 21 , 22 , 23 , 24 , 25 , 26 ]. However, limited attention has been given to studying the multigenerational effects of GO treatment, including oxidative DNA damage and epigenetic changes [ 15 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. In a study by Wang and Liu [ 15 ], the transgenerational effects of silver NPs on the gastropod L. stagnalis were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation at the N 6 position of adenine is the other major type of epigenetic modification, which has been widely recognized in bacteria and plants [9,10]. A few years ago, DNA 6mA modification was also identified in the genome of a diverse range of animal taxa ranging from worms to mammals [11][12][13][14][15]. Furthermore, the presence of 6mA was recently detected in mammalian mtDNA [16].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [21] employed C. elegans to determine the effect of long-term plastic pollution on reproductive toxicity, which found that a single long-term maternal nanoplastics exposure caused multiand trans-generational reproduction decline in the nematodes. In addition, indicators such as brood size, DNA damage, and cell apoptosis are also widely used in reproductive research [22,23]. It is still unknown whether fluopimomide has effects on DNA damage and cell apoptosis in C. elegans.…”
Section: Introductionmentioning
confidence: 99%